2014
DOI: 10.1038/jid.2013.298
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis and Disease Severity Are the Main Risk Factors for Food Sensitization in Exclusively Breastfed Infants

Abstract: Filaggrin (FLG) loss-of-function skin barrier gene mutations are associated with atopic dermatitis (AD) and transepidermal water loss (TEWL). We investigated whether FLG mutation inheritance, skin barrier impairment, and AD also predispose to allergic sensitization to foods. Six hundred and nineteen exclusively breastfed infants were recruited at 3 months of age and examined for AD and disease severity (SCORing Atopic Dermatitis (SCORAD)), and screened for the common FLG mutations. TEWL was measured on unaffec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
115
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 22 publications
9
115
0
6
Order By: Relevance
“…11 In addition, skin infections often occur in children with atopic dermatitis, and epicutaneous food exposure may be of increased consequence on skin with atopic dermatitis. 12 Skin barrier deficiency, either in the setting of epidermal mutations 8 or atopic dermatitis disease severity, 9 has been associated with food allergy and food sensitization. Skin infections may play a role in tissue-specific immune responses, which resulted in food sensitization through the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition, skin infections often occur in children with atopic dermatitis, and epicutaneous food exposure may be of increased consequence on skin with atopic dermatitis. 12 Skin barrier deficiency, either in the setting of epidermal mutations 8 or atopic dermatitis disease severity, 9 has been associated with food allergy and food sensitization. Skin infections may play a role in tissue-specific immune responses, which resulted in food sensitization through the skin.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to food allergy, skin barrier deficiencies, e.g., atopic dermatitis, have been associated with food allergy and food sensitization. 8,9 Here, we used a sample of children with and without food allergy to assess whether hygiene factors are associated with a food allergy and/or asthma diagnosis. We investigated key hygiene factors, including, antibiotic use, infections, siblings, pets, maternal child health factors and child care, and their association with food allergy and asthma in the same cohort of patients in which many showed comorbidity.…”
mentioning
confidence: 99%
“…Group A ( n = 220) consisted of 1‐year‐old children who had either never eaten egg but who had been tested for egg sensitization during infancy because of infantile eczema/atopic dermatitis, 20 or who had eliminated egg for more than 6 months due to mild egg‐induced symptoms and egg sensitization. Group B ( n = 213) consisted of 2‐ to 6‐year‐old children who had eliminated egg for more than 12 months because of a diagnosed egg allergy, confirmed by OFC or apparent egg‐induced history with documented egg sensitization, or who had never eaten egg because of egg sensitization.…”
Section: Methodsmentioning
confidence: 99%
“…Two populations are seen most commonly in daily clinics. The first population comprises children with infantile atopic dermatitis who are suspected early of food sensitization, and upon recommendation of the pediatrician have not consumed eggs during the first year of life, and now require sIgE testing to confirm allergy 20. The second population is composed of preschool children practicing egg avoidance due to confirmed egg allergy, and who require testing to determine whether the allergy has been outgrown.…”
mentioning
confidence: 99%
“…49 It is also possible that protecting the barrier from birth may reduce IgE sensitisation and the subsequent development of other allergic disease. 50 Methods Systematic reviews were identified using the 2010 UK NHS Evidence Skin Disorders Annual Evidence Updates Mapping Exercise on Atopic Eczema, which had previously identified all systematic reviews on eczema prevention published between January 2000 and August 2010.…”
Section: Introductionmentioning
confidence: 99%